Міфопоетика інфернальних образів і мотивів у романах "Майстер і Маргарита" М. Булгакова та "Перший із перших, або дорога з Лисої гори" В. Кулікова - Наместюк, С. Т. (My University, 2017)
У даній статті розглянуто вплив булгаківської традиції на твор- чість автора В. Кулікова на прикладі його роману-продовження "Пер- ший із перших, або Дорога з Лисої гори". ПроаналЬували булгаків- ську присутність, яка відображається в образах і мотивах роману. Аналізу підлягає весь сонм упирів, відьом, демонів та чортівні, яка відбувається на сторінках вищеназваних творів.
The article deals with Bulgakov's influence on the literary tradition of V. Kulikov, with his novel sequel "The first of the first, or the way from the Bald Mountain". Weanalyzed Bulgakov's presence in V. Kulikov's plots and images. The problem of Bulgakov's traditbn requires thorough study. For this, we need to expand the horizons of review of the categories of traditbn in Bulgakov and the Bulgakov's traditbns of his folbwers. The point is that to begin to analyze the impact of the great geniuses on the work of Bulgakov deviating from the false perceptbn of him as the author of actually only 'The Master and Margarita". This would allow one to understand the impact of his work on the literary process of several decades.
Keywords: теорія традиційних структур; роман-продовження; діалог культур; літературний прототип; інфернальний образ і мотив; theory of traditional structures; novel sequel; the dialogue of cultures